In the name of humanity : the secret deal to end the Holocaust - Wallace, Max (Skyhorse Publishing, 2018)
"Early in the morning of November 26, 1944, prisoners at Auschwitz heard a deafening explosion. Emerging from their barracks, they witnessed the crematoria--part of the largest killing machine in human history--come crashing down. Most assumed they had fallen victim to inmate sabotage and thousands gave a silent cheer. However, the Final Solution's most efficient murder apparatus had not been felled by Jews, but rather by the ruthless architect of mass genocide, SS chief Heinrich Himmler--an edict that has puzzled historians for more than six decades. Holocaust historian and New York Times bestselling author Max Wallace--a veteran interviewer for Steven Spielberg's Shoah Foundation--draws on an explosive cache of recently declassified documents and an account from the only living eyewitness to unravel the mystery. For the first time, he reveals an incredible story involving the secret negotiations of an unlikely trio--a former fascist President of Switzerland, a courageous Orthodox Jewish woman, and Himmler himself--to end the Holocaust, aided by clandestine Swedish and American intelligence efforts. He documents their efforts to deceive Himmler, successfully prevent the extermination of hundreds of thousands of Jews during the last months of the Second World War, and thwart Hitler's plan to take "every last Jew" down with the Reich. These are revelations that will help rewrite the history of the Holocaust and the Second World War."--